Glial Fibrillary Acidic Protein Is Not an Early Marker of Injury in Perinatal Asphyxia and Hypoxic–Ischemic Encephalopathy - Looney, Ann-Marie; Ahearne, Caroline; Boylan, Geraldine B.; Murray, Deirdre M. (Frontiers in Neurology, 2015)
Brain specific glial fibrillary acidic protein (GFAP) has been suggested as a potential biomarker for hypoxic ischaemic encephalopathy (HIE) in newborns (1, 2). Previous studies have shown increased levels in postnatal blood samples. However its ability to guide therapeutic intervention in HIE is unknown. Therapeutic hypothermia for HIE must be initiated within 6 hours of birth, therefore a clinically useful marker of injury would have to be available immediately following delivery. The goal of our study was to examine the ability of GFAP to predict grade of encephalopathy and neurological outcome when measured in umbilical cord blood. Infants with suspected perinatal asphyxia (PA) and HIE were enrolled in a single, tertiary maternity hospital, where umbilical cord blood (UCB) was drawn, processed and bio-banked at birth. Expression levels of GFAP were measured by ELISA. In total 169 infants (83 controls, 56 PA, 30 HIE) were included in the study. GFAP levels were not increased in UCB of case infants (PA/HIE) when compared to healthy controls or when divided into specific grades of HIE. Additionally, no correlation was found between UCB levels of GFAP and outcome at 36 months.